Evaluasi Program Promosi Kesehatan untuk Menurunkan Angka Stunting di Puskesmas Bandarharjo - Kurnia Lintang Larasati; Irwan Budiono; Oktia Woro Kasmini Handayani (Pusat Riset dan Inovasi Nasional, 2025)
Stunting remains a major public health concern in Indonesia, including in densely populated urban areas such as Bandarharjo, Semarang. Stunting is caused by chronic malnutrition and recurrent infections during the first 1,000 days of life (WHO, 2015). This study aims to evaluate the implementation of health promotion programs in reducing stunting rates in the Bandarharjo Community Health Center (Puskesmas) service area. This study employs a qualitative approach using the CIPP evaluation model (Context, Input, Process, Product) to assess the extent to which the program is implemented and effective in practice. Data were collected through in-depth interviews with key informants and triangulation, including health promotion officers, nutritionists, midwives, environmental health workers, Posyandu cadres, and mothers of infants. The results indicate that the program is functioning reasonably well in terms of education and cross-sectoral collaboration; however, challenges remain, including low community awareness, physical environmental barriers, and limitations in personnel and facilities. Innovations such as “Srigunting” add value to program implementation. The CIPP evaluation revealed that interventions are occurring at all stages; however, strengthening is needed in the process and monitoring aspects to ensure more optimal and sustainable outcomes.